The photothermal transparent transducer method applied to the spectroscopy of liquids - de Paula, M. H.; Lemos, G. M.; do Amaral, M. S.; Nunes, J. R.; Lourenco, A.; de Carvalho, A. A. [UNESP]; Kitano, C. [UNESP]; da Silva, J. G. [UNESP]; Sakamoto, W. K. [UNESP]; Siqueira, O. S.; Mello, G. A. B.; Pinto, J. O. P.; et al. (Elsevier B.V. Sa, 2009)
A new kind of spectroscopy of liquids is presented: the photothermal transparent transducer method applied to the spectroscopy of liquid samples. The liquid sample is placed in a small (approximately 20 ml) chamber with a LiTaO(3) pyroelectric crystal as window. The sample excitation and signal analysis could be made using modulated or pulsed techniques. Samples with low to high absorbance could be easily analyzed, including on-line experiments. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Spectroscopy of liquids; Photothermal spectroscopy of liquids; Photothermal transparent transducer; method applied to liquid samples; Photothermal spectroscopy